Ischemia/reperfusion activates myocardial innate immune response: the key role of the toll-like receptor - Vilahur, Gemma; Badimon, Lina (Frontiers in Physiology, 2014)
Recent data have indicated that the myocardium may act as an immune organ initiating cardiac innate immune response and inflammation. It has been suggested that activation of the immune system occurs upon the interaction of damage-associated molecular patterns (DAMPs) generated and released during ischemic damage with pattern recognition receptors (Toll like receptors; TLR) present in cardiac cells. Among TLRs, TLR4 and TLR2 are the ones mostly expressed in cardiac tissue. Whereas TLR4 has shown to play a detrimental role in myocardial ischemia/reperfusion (I/R) injury, the effect elicited by TLR2 activation remains controversial. Once activated, TLR signaling may occur via the Myd88- and Trif- dependent pathways leading to NFκB and IFN-3 activation, respectively, and subsequent stimulation of pro-inflammatory and immunomodulatory cytokine gene expression. Cytokine release contributes to neutrophils activation, recruitment, adhesion and infiltration to the site of cardiac injury further perpetuating the inflammatory process. This mini-review will focus on the current knowledge regarding the role of the heart in inducing and coordinating the innate inflammatory response via the TLR signaling pathway in myocardial I/R injury.